Effect of Cnidoscolus aconitifolius Leaf Extract in Lowering Triglyceride Levels and Body Weight of Wistar Rats with Metabolic Syndrome - Sarsanti, Arifa Sherina Noor; Putranto, R. Prihandjojo Andri; Sarsono, Sarsono; Nurwati, Ida; Baihaqy, Fathu Thaariq (Althea Medical Journal, 2024)
Background: Cnidoscolus aconitifolius has the potential to be antidyslipidemic which has the effect of lowering triglyceride levels. This study aimed to explore the effect of Cnidoscolus aconitifolius leaf extract on triglyceride levels and body weight of Wistar rats with metabolic syndrome.Methods: This randomized controlled trial with a pre- and posttest design was conducted in 2021 at the Center for Food and Nutrition Studies, Yogyakarta, Indonesia. Male Wistar rats were subjected into metabolic syndrome state with a high-fat and high-fructose diet (HFHFD) for 21 days, then injected with Streptozotocin (STZ, 45 mg/kg) and Nicotinamide (NA, 110 mg/kg), and designated as positive control group. The intervention group was given 150 mg/kg, 300 mg/kg, and 450 mg/kg dose of leaf extract for 28 days. Triglyceride, glucose, high-density lipoprotein or HDL, and cholesterol were measured before and after intervention, using serum samples taken from the retro-orbital vein and analyzed using an enzymatic colorimetric method. The Wistar weight was measured every week. Data was analyzed by paired T-test and One-way ANOVA with Post-hoc Bonferroni and Games-Howell.Results: There was a significant decrease in triglyceride levels after the intervention (p< 0.005). Interestingly, there was also a significant increase in weight gain in all groups after the intervention (p=0.000), both were dose dependent.Conclusion: Cnidoscolus aconitifolius leaf extract is significantly lowering triglyceride levels in the Wistar rats model. In addition, weight gain has also been observed after intervention. Clinical studies are needed to further explore the potential of Cnidoscolus aconitifolius leaves as anti-dyslipidemia.